EXPECTATIONS IMPACT ON THE EFFECTIVENESS OF THE INFLATION-REAL ACTIVITY TRADE-OFF - DAVID, Gbaguidi S. (Theoretical and Practical Research in Economic Fields, 2011)
The current study takes place in the Phillips curve framework in which first, we look at determining econometrics models leading to characterize the dynamics of the main variables underlying the trade-off in univariate contexts. As a result, it appears that an adequate way to characterize the agents' expectations regarding the dynamics of these variables is to consider a combination of some fixed levels (regimes) in the variables evolutions with an agents' adaptive beliefs notion. This expectation process is empirically captured by a Markov Switching Intercept Heteroskedastic-AutoRegressive (MSIH-AR) model. Finally, based on the implied expectations value of the variables, we show that the Phillips curve seems to disappear when the expected inflation rate's impact on its current value converges to its long-term value.